Overweight and obesity among Orang Asli adults in Krau Wildlife Reserve, Pahang: a four-year follow-up study - Chua, Ee Yin; Mohd Shariff, Zalilah; Sulaiman, Norhasmah; Appannah, Geeta (Nutrition Society of Malaysia, 2019)
Introduction: Obesity and excess weight gain in adults are linked to an increased risk of cardiometabolic abnormalities. The changing lifestyle experienced by the Orang Asli predisposes the population to the risk of obesity and non-communicable diseases. This study aimed to describe the prevalence of overweight and obesity as well as body-weight change over a period of four years among Orang Asli adults. Methods: Data were collected from Orang Asli adults aged ≥18 years, who were enrolled in the 2011-2012 and 2015-2016 surveys, and who were residing within the Krau Wildlife Reserve. Weight and height of the adults (N2011-2012=828; N2015- 2016=662) were measured at both time points. Follow-up data were available for 378 adults (male:113; female:265). Results: The prevalence of overweight and obesity were 18.8% and 7.4% in 2011-2012 and 26.1% and 9.5% in 2015-2016. In the follow-up group, significant differences in body weight and body mass index (BMI) were observed in men and women, respectively. More than one-third (35.5%) of the adults had weight gain of more than 5.0%. The increasing percentage of body weight change was associated with being female, younger age, more years of schooling and reduced household income. Conclusion: Obesity is a growing health problem in the Orang Asli adult population. Weight gain was associated with socioeconomic indicators and it was more prominent in women. Effective strategies are needed to address the increasing prevalence of overweight and obesity in this population to further reduce adverse health outcomes.